EXPLORING FACTORS INFLUENCING TRAINING EFFECTIVENESS TOWARD JOB PERFORMANCE OF FIVE STARS HOTEL IN BANGKOK: A CASE OF ABC HOTEL - Buddeekham, Sirianong; Tantasanee, Somchai (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
The researcher explores factors influencing training effectiveness toward job performance of Five Stars Hotel in Bangkok: A case of ABC Hotel. The methodology of the research integrated both quantitative and qualitative analysis. The research finding from quantitative analysis illustrated the most critical factors influence training effectiveness which are transfer knowledge and organization support. From qualitative analysis, not only these two variables critical influencing training effectiveness, but also develop needs awareness and motivation to learn among these employees. The statistical used of quantitative analysis are Pearson’s Correlation, Simple Linear Regression, Multiple Linear Regression ,One-way Anova and interview as a qualitative analysis.